Reflective Learning to Improve Teaching Abilities of Vocational High School Teacher Candidates - Khalsiah Khalsiah; Siraj Siraj; Syafirly Ramadhana; Putri Meurah Intan (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2024)
The purpose of this study is to test the effectiveness of the reflective learning model in improving the understanding and teaching skills of prospective teachers in vocational high schools. This research is a qualitative descriptive study with a case study approach. The subjects of this study are students of the Vocational Education in Mechanical Engineering. Data collection in this study used three techniques: in-depth interviews, participant observation and documentation study The data analysis technique used is the interactive model which includes: data reduction, data presentation, and conclusion drawing Implementation of the verification technique is based on four criteria: credibility, transferability, dependability, and confirmability. The conclusion of this study shows that the reflective learning model has a significant positive impact on improving the understanding and teaching skills of prospective Vocational High School teachers. The implementation of this model has been proven effective in helping prospective teachers develop their professional competencies. In addition, the students showed high involvement in the reflection process, which allowed them to evaluate and improve their teaching strategies. The majority of students also felt that reflective learning was very beneficial in enhancing their teaching skills and in preparing them to face challenges in the field of education.